Satellite orbit determination using satellite gravity gradiometry observations in GOCE mission perspective - A. Bobojć; A. Drożyner (Advances in Geosciences, 2003)
Between the years 2004 and 2005 the launch of the first gradiometric satellite is planned. This satellite will be an important element of the Gravity Field and Steady – State Ocean Circulation Explorer Mission (GOCE). This mission is one of the reasons for performing the simulation research of the Satellite Gravity Gradiometry. Our work contains the theory description and simulation results of the satellite orbit determination using the gravity tensor observations. In the process of the satellite orbit determination the initial dynamic state vector corrections are obtained. These corrections are estimated by means of the gravity gradiometry measurements. The performed simulations confirm the possibility of satellite orbit determination by means of the gravity tensor observations. Key words. satellite geodesy, satellite gradiometry, satellite orbits